2023
DOI: 10.3233/bme-230027
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of crosslinked bovine pericardium as potential scaffold for the oral cavity

Abstract: BACKGROUND: Bovine pericardium (BP) is a scaffold widely used in soft tissues regeneration; however, its calcification in contact with glutaraldehyde, represent an opportunity for its application in hard tissues, such as bone in the oral cavity. OBJECTIVE: To develop and to characterize decellularized and glutaraldehyde-crosslinked bovine pericardium (GC-BP) as a potential scaffold for guided bone regeneration GBR. METHODS: BP samples from healthy animals of the bovine zebu breed were decellularized and crossl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
0
0
0
Order By: Relevance
“…The investigation revealed that GC-BP displayed conformational alterations in collagen molecules, leading to reduced mechanical properties while enhancing cell adhesion and viability of dental pulp stem cells. These findings suggest that GC-BP holds promise as a potential candidate for GBE [ 8 ]. Genetic toxicity testing is crucial for assessing the safety of materials employed in GTR.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation revealed that GC-BP displayed conformational alterations in collagen molecules, leading to reduced mechanical properties while enhancing cell adhesion and viability of dental pulp stem cells. These findings suggest that GC-BP holds promise as a potential candidate for GBE [ 8 ]. Genetic toxicity testing is crucial for assessing the safety of materials employed in GTR.…”
Section: Introductionmentioning
confidence: 99%